TQM PRACTICES AND QUALITY MANAGEMENT PERFORMANCE - A CASE STUDY ON IKEA, BANGALORE CITY - STALIN S, Mr. JOSWA; Mr. Sujay C; Vardhana Rao, Mr. P.Swetha (The journal of contemporary issues in business and government, 2022)
Total Quality Management (TQM) is a process that enhances the continuous development of products and service quality to getcustomer satisfactionand promote theproductivity.Quality management is managing all the activities which determine the quality policy andhow implementation by the quality planning and quality assurance.Ithas abig role toimprove and develop the performance of the organization. Therefore, this study investigatesthe effect of quality management practices on company financial performance. This researchused both qualitative and quantitative approaches such as literature review and questionnaire.There are about 53 respondents from IKEA Company;Bangalore City had participated in thisstudy. The questionnaire is used to understand the perspective of employees regarding theimportance of quality management practices on company financial performance. This study identified three main practices : management , infrastructure , corepracticesandtheirrelationship with the company financial performance. The hypotheses test results confirmedthat there is a positive relationship between the quality management practices and companyfmancialperformance.